(untitled) (International Journal of Innovative Research in Engineering & Management, 2023)
The distinction between B2B and "mainstream" advertising reflects the limitations of the traditional, goods-dominant (G-D) model of commerce and a value creation paradigm based on the "producer" vs. "consumer" divide. Customer (S-D) logic expands the understanding of exchange and value creation by stating that all social and economic actors participating in commerce (e.g., corporations, customers, etc.) are service delivering, value-creating organizations; hence, any transaction may be classified as B2B in this sense. B2B marketing (along with other sub-disciplines) may be considered relevant to’mainstream’ marketing from this perspective. This broad, actor-to-actor (A2A) methodology leads to a dynamic, interconnected, and systemic approach to value creation. This article looks at how this system works as a computing architecture and the steps that need to be taken to turn it into a theoretical market model influenced by advertisement sub disciplines, marketing programmes, and sciences beyond of business.